Implementasi Model Pembelajaran Cooperative Learning Tipe Rotating Trio Exchange (Rte) Dalam Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Bahasa Arab Kelas VIII SMPS Plus As - Sa’adah 2 Sukadiri - Nurul Fathona; Faedurrohman (INTIFA: Journal of Education and Language, 2024)
ABSTRACT This study aims to analyze the implementation of the Cooperative Learning model, specifically the Rotating Trio Exchange (RTE) type, in improving students’ learning outcomes in Arabic subjects for Grade VIII at SMPS Plus As-Sa’adah 2 Sukadiri. The background of this research stems from the low achievement in Arabic learning, caused by conventional teaching methods and minimal student interaction. This research uses a qualitative descriptive approach with data collected through observation, interviews, and documentation. The results show that the RTE model enhances student participation, motivation, and understanding of the material. The rotating group discussions encourage critical thinking, opinion exchange, and the development of social and communication skills. Although challenges such as limited time and initial difficulty in understanding the rotation procedure exist, they can be overcome with active teacher guidance. Overall, the RTE model proves effective in improving students’ cognitive, affective, and psychomotor learning outcomes while fostering a more active and collaborative learning environment. ABSTRAK Penelitian ini bertujuan menganalisis penerapan model Cooperative Learning tipe Rotating Trio Exchange (RTE) dalam meningkatkan hasil belajar Bahasa Arab siswa kelas VIII SMPS Plus As-Sa’adah 2 Sukadiri. Latar belakangnya adalah rendahnya hasil belajar akibat metode konvensional dan minimnya interaksi aktif siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan teknik observasi, wawancara, dan dokumentasi. Hasilnya menunjukkan bahwa model RTE mampu meningkatkan partisipasi, motivasi, serta pemahaman siswa. Diskusi bergilir dalam kelompok kecil mendorong siswa berpikir kritis, bertukar pendapat, dan mengembangkan keterampilan sosial. Meski terdapat kendala seperti keterbatasan waktu dan kesulitan memahami prosedur rotasi, hal ini dapat diatasi melalui bimbingan guru. Secara keseluruhan, model RTE efektif dalam meningkatkan hasil belajar siswa, baik dalam ranah kognitif, afektif, maupun psikomotorik, serta menciptakan suasana belajar yang lebih aktif dan kolaboratif.